Samdráttur – Æfing 2 – Lausnir

  1. a – b + (3b – 2a) + 4a + (a – b) = a – b + 3b – 2a + 4a + a – b = a(1 – 2 + 4 + 1) + b(-1 + 3 – 1) = 4a + b
  2. a – (b + 3b) – 2a – (4a + a – b) = a – b – 3b – 2a – 5a + b = a(1 – 2 – 5) + b (-1 – 3 +1) = -6a – 3b
  3. 2x + 9y + 14z – 22x – 34y + 15 x – 41y + 3z = x(2 – 22 + 15) + y(9 – 34 – 41) + z(14 + 3)
    1. = -5x – 66y + 17z
  4. 4p – 3p2q·(-2 +7) + pq(-4-5) + (21 – 9) – 11p3q = 4p – 15 p2q – 9pq + 12 – 11p3q
  5. 4a – (2b – d) – (3a – 2b – (4c – d) + 3c)
  6. 5a – (5x + (2x – k) – 4k + (a – (2x -2k)+x)) = 5a – (5x + 2x – k – 4k + (a -2x + 2k +x)) = 5a – (7x – 5k + a – x + 2k) = 5a – (6x – 3k + a) = 5a – 6x + 3k – a = 4a – 6x + 3k